Sheehan Syndrome: a Rare Complication of Post-partum Hemorrhage - Soni, M (Nepal Journal of Obstetrics and Gynaecology, 2014)
Incidence of Sheehan syndrome, also known as post-partum hypopituitarism or post-partum pituitary insufficiency or hypopituitarism syndrome has reduced markedly but it does occur in under-developed countries with a reported incidence of 1:10000 deliveries.1-3 We are reporting the case of a 22 year old female with Sheehan syndrome occurring after massive post-partum hemorrhage. DOI: http://dx.doi.org/10.3126/njog.v9i2.11766